Uporaba informacijsko-komunikacijske tehnologije pri poučevanju in učenju angleščine v otroštvu - Brumen, Mihaela; Krušič, Helena; Zupančič, Tomaž (Revija za elementarno izobraževanje, 2017)
The Use of ICT in English Language Teaching and Learning in the Primary Education. The article introduces the use of ICT in teaching English as a foreign language to young learners. It describes a comparative study within three countries, Slovenia, Spain, and Turkey, including 313 teachers. The research is a part of the large-scale EU project SBATEYL (2014-1-TR01- KA201-013197). It is based on the descriptive and causal non-experimental method of empirical pedagogical research. The study explores foreign language teachers’ basic knowledge about web technologies and the level of the use thereof in classes. The results show that Slovenian teachers, teaching a foreign language to young learners, do not use computer technologies (virtual worlds, blogs, computer games, digital stories, audio materials) as often as their Spanish or Turkish colleagues.
Keywords: early English; ICT; project SBATEYL; comparative study; curriculum